О МЕРОПРИЯТИЯХ РАБОЧИХ ГРУПП ПРОЕКТА КАСПЭКО, НАПРАВЛЕННЫХ НА ВОССТАНОВЛЕНИЕ ИСТОЩЕННЫХ РЫБНЫХ РЕСУРСОВ КАСПИЙСКОГО МОРЯ (Eurasian Journal of Ecology, 2016)
The activities of working groups comprised of national experts from all the Caspian littoral states of the UNDP-GEF CASPECO project aimed at restoring depleted fish stocks of the Caspian Sea on ecosystem-based management of aquatic bioresources and the strengthening of the regional environmental governance are discussed. The project supports the Caspian countries efforts to further halt the decline in bioresources and to restore depleted fisheries of the Caspian Sea. The main outputs of CASPECO’s working groups on ecosystem-based management of bioresources (EBBM), the inventory of. fish spawning grounds and fish passage facilities are provided.